2021
DOI: 10.3390/metabo11020084
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Metabolomic Approach Shows that Wheat Interferes with Fluorescent Pseudomonas Physiology through Its Root Metabolites

Abstract: Roots contain a wide variety of secondary metabolites. Some of them are exudated in the rhizosphere, where they are able to attract and/or control a large diversity of microbial species. In return, the rhizomicrobiota can promote plant health and development. Some rhizobacteria belonging to the Pseudomonas genus are known to produce a wide diversity of secondary metabolites that can exert a biological activity on the host plant and on other soil microorganisms. Nevertheless, the impact of the host plant on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 95 publications
1
29
0
Order By: Relevance
“…Adular and Bordeaux plant extracts induce the modification of the production of more than half of F113 and JV395B metabolites (i.e., 53.5% and 54.2%, respectively). Furthermore, as reported in our previous work [10], the production of compounds involved in Pseudomonas plant-beneficial properties are altered in conditioned bacterial cells. For strain F113, the production of DAPG decreases, while the production its precursor the mono-acetylphloroglucinol (MAPG) increase.…”
Section: Conditioning Of Pseudomonas Cells With Wheat Extracts and Ev...supporting
confidence: 74%
See 2 more Smart Citations
“…Adular and Bordeaux plant extracts induce the modification of the production of more than half of F113 and JV395B metabolites (i.e., 53.5% and 54.2%, respectively). Furthermore, as reported in our previous work [10], the production of compounds involved in Pseudomonas plant-beneficial properties are altered in conditioned bacterial cells. For strain F113, the production of DAPG decreases, while the production its precursor the mono-acetylphloroglucinol (MAPG) increase.…”
Section: Conditioning Of Pseudomonas Cells With Wheat Extracts and Ev...supporting
confidence: 74%
“…Plant-beneficial bacteria are also able to produce bioactive metabolites that exhibit a signaling activity on plant biosynthesis pathways and influence plant growth [ 6 ]. Yet, one of our previous studies [ 10 ] showed that wheat root extracts containing bioactive metabolites can significantly influence the production of secondary metabolites by several rhizospheric Pseudomonas strains. We showed that root extracts of the wheat genotypes Adular and Bordeaux (at a concentration of 50 µg·mL −1 ) could alter the accumulation of 39% and 29% of the secondary metabolites produced by Pseudomonas ogarae F113 and 38% and 28% of those produced by Pseudomonas chlororaphis JV395B, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that the interaction with the plant increases the capacity of B. subtilis to compete with Serattia plymuthica , and our current results further indicate that the root is an active regulator of the competitive interactions occurring on its roots ( Ogran et al., 2019 ). An increase in bacterial competitiveness due to increased antibiotic production may be a conserved feature of rhizobacteria: plants enhance the killing efficiency of Xanthomonas citri by Paenibacillus polymyxa SC2 ( Liu et al., 2021 ), wheat extract induces the expression of biosynthetic genes for antibiotic production in Pseudomonas genotypes ( Rieusset et al., 2021 ), and barley induces the antifungal genes of Pseudomonas fluorescens ( Jousset et al., 2011 ). Our methodology here offers a practical approach to study the effect of plant metabolites on heterogeneous communities, even when expressed by a small subpopulation of cells, with IFC to analyze the population at the single-cell level, and luciferase-based reporters to screen for potential activators.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the Arabidopsis case revealed the detailed gene clusters responsible for root-specific metabolic pathways, wherein the specific metabolites involved selectively influence the root rhizosphere microbes ( Huang et al., 2019 ). Following this clue, the interactions of metabolites in the wheat root rhizosphere exudates with soil microbes were respectively inspected using an LC–MS-based technique ( Rieusset et al., 2021 ) and GC–MS platform ( Iannucci et al., 2021 ). Although these wheat metabolomics examinations seldom provide candidate genes for swift functional validation, as commented elsewhere ( Saia et al., 2019 ), recognizing the metabolic profiles of wheat samples under various environmental conditions or developmental stages provides a requisite knowledge for parallel and in-depth experimental designs.…”
Section: The Application Of Metabolomics In Wheat Should Deliver the Swift Detection Of A Vast Category Of Metabolitesmentioning
confidence: 99%